Evaluating the efficacy of epinastine ophthalmic solution using a conjunctivitis allergen challenge model in patients with birch pollen allergic conjunctivitis - Tagawa, Yoshiaki; Namba, Kenichi; Nakazono, Yumi; Iwata, Daiju; Ishida, Susumu (Allergology international, 2017)
The efficacy of epinastine 0.05% ophthalmic solution for pollen allergic conjunctivitis has already been shown in a conjunctival allergen challenge (CAC) test using cedar pollen as a challenge. The present study investigated the efficacy of this solution against birch pollen conjunctivitis in a CAC test. Ten adult subjects (eight males and two females) with asymptomatic birch pollen conjunctivitis were enrolled in this study. The average age of the subjects was 41.1 years. This study was conducted during a period without birch pollen dispersion. In each subject, the epinastine 0.05% ophthalmic solution was instilled in one eye, and an artificial tear fluid was instilled in the fellow eye in a double-blind manner. Five minutes or 4 h after the drug instillation, both eyes were challenged with an optimal concentration of birch pollen, and ocular itching and conjunctival hyperemia were then graded. Tears were collected before the drug instillation and 20 min after the pollen challenge, and the histamine level was measured. The ocular itching scores and palpebral conjunctival hyperemia scores of the epinastine-treated eyes were significantly lower than those of the contralateral control eyes when the eyes were pretreated with the drug 4 h before the CAC. There was a significant correlation between the tear histamine level and mean ocular itching score of three time points (3, 5 and 10 min) following the CAC in the control eyes but not the epinastine-treated eyes. Epinastine is effective in suppressing ocular itching and conjunctival hyperemia in birch pollen conjunctivitis.